The Development of Ecological Intelligence through “Madrasah” Culture - Muntaha; Tobroni; Ishomuddin; Khozin (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to describe the development of ecological intelligence for Madrasah Tsanawiyah (Islamic Junior High School) students. The researchers used a case study method to obtain the result. This method is describing further the achievement of MTsN (Public Islamic Junior High School) 1 Malang that already succeeds in developing ecological intelligence to the students through 'Madrasah’ culture, which is ecologic. The ecological culture is instilling tauhid value, integrative Islamic education curriculum, habitation, exemplary, together with movement, and supported by 'Madrasah’ vibes. So that ecological intelligence in students can be developed well.